(untitled) (Journal of the College of Basic Education, 2023)
History: Increased oxidative stress and decreased antioxidant are linked to diabetes type 2 Diabetes In diabetic people, vitamin E administration lowers oxidative stress. We aimed to gauge the amount of this vitamin using these techniques:By planning the current study, patients will be able to evaluate its impact on patient-controlled diabetes. This descriptive and cross-sectional research, which involved 186 individuals with type 2 diabetes, was conducted. Patients were put into two groups1 depending on whether their HbA1C levels were less than or greater than 7 (measured using the HPLC technique), as well as the levels of TG, cholesterol, HDL, and Cr. A check list with questions about each patient’s age and information related to their measured vitamin levels was created.